DYNAMIC ANALYSIS STUDY: IMPACT OF TIKTOK APPLICATIONS ON CHARACTER EDUCATION IN COVID-19 PANDEMIC - Rodey Hamza Bin Hamzah; Mohd Zohdi Bin Said; Udin Supriadi (Universitas Pendidikan Indonesia, 2021)
This study aims to explore an analysis of the effects of using the TikTok application as a new learning model in the arts and culture sector during the Covid-19 Pandemic. The author observes that there is a considerable change in behavior among the community, especially the millennial generation in the use of technology as a bridge for online learning, namely the increasing interest of millennials in using the TikTok application lately. The research study on this occasion was carried out with a quantitative approach, where data collection was taken using a questionnaire technique. The measurement technique uses a Likert scale from a range of 1-5. The object of the research was focused on junior high school students, which was carried out using the Random Sampling Technique in which 103 participants were recorded. The Research Question is focused on exploring the relationship of this application with a new learning approach to arts and culture. The results showed that as many as 62.1% of respondents strongly agreed to help adjust traditional dance moves, 70.9% helped memorize movement choreography, 68% helped to recognize modern dance, and 57.3% agreed that this application helps understand cultural arts learning.